How to Provide Patient Safety in the Emergency Department? A Qualitative Study Emergency Nurses' Experiences - Selin Keskin Kızıltepe; Aslı Kurtgöz (Sağlık ve Hemşirelik Yönetimi Dergisi)
Aim: This study aimed to explore the experiences of emergency nurses regarding patient safety. Method: This study, with a qualitative design, was carried out between December 2022 and March 2023 in the emergency department of a university hospital. We conducted in-depth interviews with a purposive sample of 14 emergency nurses. The data were analyzed using thematic analysis. Results: Of the participants, 50% were male. Their age ranged from 25 to 40 years (mean 32.2, SD=5.99). Through the data analysis, two themes and three sub-themes were identified: (I) difficulties specific to the emergency department, (II) factors affecting patient safety the in emergency department. Conclusion: Nurses stated that they often took individual and immediate preventive measures regarding patient safety. However, rather than individual prevention, strategies and plans are required to create an institutional patient safety culture. At the same time, administrators should adopt a proactive approach to patient safety and create a supportive environment for nurses regarding patient safety.